Tales of transition paths: Policy uncertainty and random walks - Josef Hollmayr; Christian Matthes (Deutsche Bundesbank, 2015)
What happens when fiscal and/or monetary policy changes systematically? We construct a DSGE model in which agents have to estimate fiscal and monetary policy rules and assess how uncertainty surrounding the conduct of policymakers influences transition paths after policy changes. We find that policy changes of the magnitude often considered in the literature can lead private agents to hold substantially different views about the nature of equilibrium than would be predicted by a full information analysis. In particular, random walk-like behavior can be observed for a large number of periods in equilibrium, even though the models we use admit stationary dynamics under full-information rational expectations.
Keywords: E32; D83; E62; 330; DSGE; Monetary-Fiscal Policy Interaction; Learning